Preparation method of glass substrate

By preparing conductive patterns on the glass substrate and co-sintering them after coating high-thermal conduction aluminum paste, the problem of insufficient thermal conductivity of the glass substrate is solved, and its heat dissipation ability is significantly improved. It is suitable for packaging and use of high-power LEDs.

CN113809221BActive Publication Date: 2025-06-03SHENZHEN BAROY NEW MATERIAL TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202110968214.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-08-23
Publication Date
2025-06-03
Estimated Expiration
2041-08-23

AI Technical Summary

Technical Problem

The thermal conductivity of existing glass substrates is insufficient, making it difficult to meet the heat dissipation needs of high-power LEDs.

Method used

The conductive pattern is prepared on one surface of the glass substrate, and the aluminum paste with high thermal conductivity is coated on the back surface, and then dried and sintered together to improve the thermal conductivity of the glass substrate.

Benefits of technology

Through this method, the heat dissipation ability of the glass substrate is significantly improved, making it suitable for packaging and use of high-power LED chips with high light efficiency, high heat dissipation and high integration.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113809221B_ABST
    Figure CN113809221B_ABST
Patent Text Reader

Abstract

This application relates to the field of substrate processing technologies, and particularly to a method for preparing a glass substrate. The preparation method includes the following steps: providing an initial glass substrate; preparing a conductive pattern on one surface of the initial glass substrate; coating aluminum paste on the back surface of the initial glass substrate with the conductive pattern formed thereon, performing a drying treatment, and then co-sintering to obtain a glass substrate. This preparation method has a simple process, is easy to operate, has a low cost, is environmentally friendly and pollution-free. The finally obtained glass substrate has significantly improved thermal conductivity and can be used for the packaging of high-power LED chips with high luminous efficiency, high heat dissipation and high integration. It can better improve the light-emitting and heat-dissipating performance and has good application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application belongs to the technical field of substrate processing, and particularly relates to a method for preparing a glass substrate. Background Art

[0002] With the rapid development of science and technology, people's requirements for the luminous power of lighting are getting higher and higher, and high power has become an inevitable trend. As an excellent semiconductor optoelectronic component, the Light Emitting Diode (LED) has become the ideal new generation of solid-state energy-saving lighting source with the advantages of small size, low power consumption, long service life, environmental protection, etc. The LED has the property of a cold light source, that is, its spectrum hardly contains an infrared spectrum, so heat cannot be released by the way of thermal radiation like an incandescent lamp and can only be released through other ways. There are many heat dissipation paths for the LED chip, and the most important path is to rely on the substrate for heat dissipation. Therefore, the heat dissipation ability of the substrate directly affects the product performance of high-power LED devices. Therefore, the selection of the substrate material is very important.

[0003] At present, the heat dissipation substrates applied to high-power LEDs at home and abroad generally include epoxy resin substrates (FR4), metal core printed circuit boards (Metal Core PCB, MCPCB), glass substrates, etc. The epoxy resin substrate is difficult to meet the heat dissipation requirements of medium and high-power LEDs due to its low thermal conductivity. The metal core printed circuit board is generally a sandwich structure of copper foil, insulating layer, and metal core. The insulating layer is generally a polymer material such as epoxy resin. Therefore, its thermal conductivity is greatly restricted, and the thermal expansion coefficient and the wafer matching coefficient are not high. The glass substrate has many advantages: First, it is beautiful and has good light transmittance. After the surface is mirror-treated, the reflectivity is high, which improves the light extraction rate; Second, it has good stability and can resist the influence of heat and acid; Third, it has good insulation performance; Fourth, it has low cost. The main raw material of glass is silicate, which is rich in reserves on the earth; Fifth, the process is simple and mature. However, the biggest disadvantage of glass is its low thermal conductivity. Therefore, the thermal conductivity of the glass substrate needs to be improved. Summary of the Invention

[0004] The purpose of this application is to provide a method for preparing a glass substrate, aiming to solve the technical problem of how to improve the thermal conductivity of the glass substrate.

[0005] To achieve the above application purpose, the technical solution adopted in this application is as follows:

[0006] This application provides a method for preparing a glass substrate, including the following steps:

[0007] Provide an initial glass substrate;

[0008] Prepare a conductive pattern on one surface of the initial glass substrate;

[0009] Apply aluminum paste on the back side of the initial glass substrate formed with the conductive pattern, perform a drying treatment, and then co-sinter to obtain a glass substrate.

[0010] The method for preparing a glass substrate provided in this application is obtained by applying aluminum paste with a high thermal conductivity coefficient on the back side of a glass substrate with a conductive pattern and then co-sintering. The aluminum paste co-sintered on the back side of this glass substrate can quickly and effectively transfer the heat on the glass substrate, so the heat dissipation capacity is significantly improved compared with the existing glass substrate; moreover, this preparation method has a simple process, is easy to operate, has a low cost, is environmentally friendly and pollution-free. The finally obtained glass substrate has significantly improved thermal conductivity and can be applied to the packaging of high-power LED chips with high luminous efficiency, high heat dissipation, and high integration, and can better improve the light output and heat dissipation performance, and has good application prospects. Description of the Drawings

[0011] In order to more clearly illustrate the technical solutions in the embodiments of this application, the following will briefly introduce the drawings required for the description of the embodiments. Obviously, the drawings in the following description are only some embodiments of this application. For those of ordinary skill in the art, without creative efforts, other drawings can also be obtained based on these drawings.

[0012] Figure 1 It is a process flow schematic diagram of a method for preparing a glass substrate provided in an embodiment of this application. Detailed Embodiments

[0013] In order to make the technical problems to be solved, technical solutions and beneficial effects of this application clearer, the following further details this application in combination with embodiments. It should be understood that the specific embodiments described here are only used to explain this application and are not used to limit this application.

[0014] In this application, the term "and / or" describes the association relationship of associated objects and indicates that three relationships can exist. For example, A and / or B can represent: A exists alone, A and B exist simultaneously, and B exists alone. Where A and B can be singular or plural. The character " / " generally represents an "or" relationship between the associated objects before and after.

[0015] In this application, "at least one" means one or more, and "a plurality" means two or more. "At least one of the following (items)" or its similar expression refers to any combination of these items, including any combination of single (item) or plural (items).

[0016] It should be understood that in various embodiments of the present application, the sequence numbers of the above processes do not mean the order of execution. Some or all of the steps can be executed in parallel or sequentially. The execution order of each process should be determined according to its function and internal logic, and should not constitute any limitation to the implementation process of the embodiments of the present application.

[0017] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms of "a", "the", and "said" used in the embodiments of the present application and the appended claims are also intended to include the plural forms, unless the context clearly indicates otherwise.

[0018] The weight of the relevant components mentioned in the specification of the embodiments of the present application not only can refer to the specific content of each component, but also can represent the proportional relationship of the weights between the components. Therefore, as long as the content of the relevant components in the specification of the embodiments of the present application is enlarged or reduced in proportion, it is within the scope disclosed in the specification of the embodiments of the present application. Specifically, the mass described in the specification of the embodiments of the present application can be mass units well-known in the chemical industry such as μg, mg, g, kg, etc.

[0019] The first aspect of the embodiments of the present application provides a method for preparing a glass substrate, and the preparation method includes the following steps:

[0020] S01: Provide an initial glass substrate;

[0021] S02: Prepare a conductive pattern on one surface of the initial glass substrate;

[0022] S03: Coat aluminum paste on the back surface of the initial glass substrate formed with the conductive pattern, perform a drying treatment, and then co-sinter to obtain the glass substrate.

[0023] The method for preparing a glass substrate provided by the embodiments of the present application is a method for preparing a glass-based circuit board. The thermal conductivity of the glass substrate obtained by this preparation method is significantly improved, and the heat dissipation problem of the glass substrate can be well solved. Specifically, the initial glass substrate has two opposite surfaces. In the embodiments of the present application, a conductive pattern is prepared on one surface of the initial substrate, and aluminum paste with a high thermal conductivity is coated on the other surface, that is, the back surface of the initial glass substrate formed with the conductive pattern, and then co-sintered. The aluminum paste co-sintered on the back surface of the glass substrate can quickly and effectively transfer the heat on the glass substrate, so the heat dissipation ability of the glass substrate is significantly improved compared with the existing glass substrate. Moreover, this preparation method has a simple process, is easy to operate, has a low cost, is environmentally friendly and pollution-free. The finally obtained glass substrate has significantly improved thermal conductivity and can be applied to the packaging of high-power LED chips with high luminous efficiency, high heat dissipation, and high integration, and can better improve the light output and heat dissipation performance, and has a good application prospect.

[0024] In the above step S01: The initial glass substrate provided is a glass sheet, that is, the glass sheet used to prepare the glass-based circuit board. In the embodiments of the present application, the selected glass sheet has a thickness of 0.3 to 3 mm, preferably a glass sheet with a thickness of 1 to 3 mm.

[0025] In the above step S02: The step of preparing the conductive pattern on one surface of the initial glass substrate includes: printing the conductive paste on the initial glass substrate through a pattern screen, and then baking at 80 to 200 °C.

[0026] Among them, the pattern screen is a silk screen or a steel screen. According to the product performance requirements, the conductive paste is selected and directly printed on the glass sheet with the corresponding pattern screen to obtain a glass sheet coated with the conductive paste. Then baking at 80 - 200 °C can make the organic solvent in the conductive paste volatilize better, thereby pre-forming the glass sheet plate with the conductive pattern.

[0027] The above conductive paste can be one or several of conductive silver paste, conductive copper paste, conductive nickel paste, and conductive aluminum paste. Specifically, based on the total weight of the conductive paste being 100%, the conductive paste includes the following components in weight percentage: 70 - 90% of metal powder, 0.5 - 20% of inorganic binder, 5 - 15% of organic solvent, 0 - 5% of film-forming aid, and 0 - 5% of other additives. The metal powder is selected from at least one of copper powder, silver powder, aluminum powder, and nickel powder, so as to obtain different types of conductive pastes. The size of the metal powder can be 0.3 - 20 μm, specifically one or a mixture of several of the spherical, flaky, and dendritic metal powders within the above size range. The inorganic binder is a glass powder with a softening point of 300 - 650 °C. The organic solvent is selected from at least one of diethylene glycol monobutyl ether, diethylene glycol butyl ether acetate, terpineol, and dodecyl acetate. The film-forming aid is selected from at least one of ethyl cellulose, acrylic resin, and cellulose acetate butyrate. The other additives are selected from at least one of commercially available dispersants, thixotropic agents, leveling agents, and defoamers. The preparation of the conductive paste can include: adding the above-mentioned amounts of metal powder, inorganic binder, organic solvent, film-forming aid, and other additives into a suitable container, pre-stirring and mixing, and then grinding and dispersing with a three-roll mill to obtain a conductive paste with a suitable fineness.

[0028] Furthermore, the metal powder content can be 70%, 75%, 80%, 85%, 90%, etc.; the inorganic binder content can be 0.5%, 1%, 5%, 8%, 10%, 15%, 18%, 20%, etc.; the organic solvent can be 5%, 8%, 10%, 12%, 15%, etc.; the film-forming aid can be 0%, 1%, 2%, 4%, 5%, etc.; the other additives can be 0%, 1%, 2%, 4%, 5%, etc.

[0029] In the above step S03: Aluminum paste is coated on the back surface of the glass substrate formed with a conductive pattern, dried, and then co-sintered to obtain the glass substrate. A conductive pattern is prepared on one surface of the glass substrate, and aluminum paste is coated on the back surface of the conductive pattern by printing. It is baked and dried at 80-200 °C to volatilize the organic solvent in the aluminum paste, so as to better carry out sintering. Further, the temperature of the co-sintering after printing the aluminum paste is 400-700 °C. The co-sintering can be carried out in a sintering furnace, and air atmosphere sintering can be selected, or hydrogen-nitrogen mixed atmosphere sintering can also be selected.

[0030] Further, after the drying treatment and before the co-sintering, a degumming pre-curing treatment can be carried out first. The temperature of the degumming pre-curing is 350-450 °C, and the time is 15-25 min. Under the above conditions, degumming and degreasing can be better carried out, and the organic components can be fully burned, decomposed and volatilized.

[0031] The aluminum paste coated on the back surface of the above glass substrate is high thermal conductivity aluminum paste. Based on the total weight of 100%, it includes the following components in weight percentage: 70-90% of aluminum powder, 0.5-20% of inorganic binder, 5-15% of organic solvent, 0-5% of film-forming aid, and 0-5% of other aids. The selection of the inorganic binder, organic solvent, film-forming aid and other aids refers to the above text. Among them, the size of the aluminum powder can be 0.3-10 μm, and preferably 0.3-0.5 μm aluminum powder.

[0032] The glass substrate of the embodiment of the present application is prepared by the above preparation method. The thermal conductivity of the glass substrate finally obtained by this preparation method is significantly improved. Therefore, it has good thermal conductivity. Specifically, in the embodiment of the present application, a conductive paste is first printed on one side of the glass sheet to make a conductive circuit. After baking and pre-curing, a thermal conductivity aluminum paste is printed on the other side of the glass sheet as a thermal conductivity area. Finally, the glass substrate with the thermal conductivity area and the conductive circuit is co-sintered at 400-700 °C. The metal fillers in the conductive paste and the thermal conductivity aluminum paste are oxidized during the sintering process, and a chemical reaction occurs with the surface of the glass substrate to form a bonding layer, enhancing the adhesion between the paste layer and the substrate; at the same time, both the conductive paste and the thermal conductivity aluminum paste contain glass powder fillers, and according to the principle of similar phase melting, a physical reaction can occur with the glass substrate, making the paste bond more firmly with the glass substrate. Thus, a glass-based circuit board with a thermal conductivity area and a conductive circuit is obtained. The thermal conductivity aluminum paste used in this glass-based circuit board has an extremely high thermal conductivity and can quickly and effectively transfer the heat on the glass substrate, and the heat dissipation ability is greatly improved compared with the glass-based circuit board without coating the thermal conductivity aluminum paste on the back surface. Therefore, the glass substrate obtained in this way can be used for the packaging of high luminous efficiency, high heat dissipation, and high integration high-power LED chips, significantly improving the light output and heat dissipation performance.

[0033] As Figure 1As shown in the figure, the preparation method of the glass substrate in the embodiment of the present application includes: preparing conductive paste, patterning the conductive paste, baking and preforming, printing aluminum paste, and co-sintering. Specifically, (1) Preparation of conductive paste: Add metal powder, inorganic binder, organic solvent, film-forming aid, and additive into a suitable container, pre-stir and mix, and then grind and disperse with a three-roll grinder to obtain a conductive paste with appropriate fineness. (2) Patterning of conductive paste: According to the product performance requirements, select the conductive paste and directly print it on the glass sheet with a corresponding pattern screen to obtain a glass sheet coated with conductive paste. (3) Baking and preforming: Put the above-mentioned patterned glass sheet into a blast drying oven and bake it at 80-200 °C to volatilize the solvent of the conductive paste and preform it. (4) Printing aluminum paste: Print high-thermal-conductivity aluminum paste on the back of the above-mentioned preformed glass sheet, and then put it into the blast drying oven again to bake and dry to obtain a glass-based circuit board with aluminum paste coated on the back; (5) Co-sintering: Put the glass-based circuit board with aluminum paste coated on the back into a sintering furnace and sinter it at 400-700 °C to obtain a glass-based circuit board with a high thermal conductivity coefficient.

[0034] The glass-based circuit board prepared by the above preparation method in the embodiment of the present application has a simple process, is easy to operate, environmentally friendly and pollution-free, does not increase the discharge of three wastes, is harmless to operators, has a low substrate cost, and the thermal conductivity is significantly improved. It is easy to mass-produce and can be applied to high-power LED packages with high luminous efficiency, high heat dissipation, and high integration, and has good commerciality.

[0035] The following is an illustration with specific embodiments.

[0036] Example 1

[0037] A preparation method of a copper circuit glass-based circuit board includes the following steps:

[0038] 1. Weigh 81 g of copper powder with a particle size of 0.3-0.5 μm, 9 g of glass powder, 6 g of diethylene glycol monobutyl ether, 2 g of dodecyl alcohol ester, 0.5 g of ethyl cellulose, 0.9 g of dispersant, and 0.6 g of thixotropic agent into a container, pre-stir and mix, and then grind and disperse with a three-roll grinder to obtain a conductive copper paste with a blade fineness <5 μm;

[0039] 2. Weigh 71.25 g of aluminum powder with a particle size of 1-2 μm, 3.75 g of glass powder, 16 g of diethylene glycol monobutyl ether, 4.3 g of dodecyl alcohol ester, 3.75 g of ethyl cellulose, 0.75 g of dispersant, and 0.2 g of thixotropic agent into a container, pre-stir and mix, and then grind and disperse with a three-roll grinder to obtain a high-thermal-conductivity aluminum paste with a blade fineness <5 μm;

[0040] 3. Screen-print the above-prepared conductive copper paste on a 2-mm ordinary glass sheet with a corresponding pattern to obtain a glass sheet printed with conductive copper paste;

[0041] 4. Place the glass slides prepared above into a forced-air drying oven and bake them at 120 °C for 15 minutes to form the shape.

[0042] 5. Print the prepared high thermal conductivity aluminum paste on the back of the glass slide printed with the conductive copper paste above, and then place it in the forced-air drying oven again to bake and form the shape, obtaining a glass slide printed with the conductive copper paste and the thermal conductivity aluminum paste.

[0043] 6. Subject the glass slide printed with the conductive copper paste and the thermal conductivity aluminum paste above to degumming and pre-curing in a muffle furnace at 400 °C for 20 minutes.

[0044] 7. Place the degummed glass slide above into a hydrogen-nitrogen mixed atmosphere furnace, sinter and reduce it at 700 °C for 20 minutes to obtain a high thermal conductivity copper circuit glass-based circuit board.

[0045] Example 2

[0046] A method for preparing a copper circuit glass-based circuit board, comprising the following steps:

[0047] 1. Weigh 81 g of copper powder with a particle size of 0.3 - 0.5 μm, 9 g of glass powder, 6 g of diethylene glycol monobutyl ether, 2 g of dodecyl alcohol ester, 0.5 g of ethyl cellulose, 0.9 g of dispersant, and 0.6 g of thixotropic agent and add them to a container, pre-stir and mix, and then grind and disperse with a three-roll mill to obtain a conductive copper paste with a scraping fineness < 5 μm.

[0048] 2. Weigh 80.75 g of aluminum powder with a particle size of 1 - 2 μm, 4.25 g of glass powder, 8 g of diethylene glycol monobutyl ether, 4.65 g of dodecyl alcohol ester, 1.2 g of ethyl cellulose, 0.85 g of dispersant, and 0.3 g of thixotropic agent and add them to a container, pre-stir and mix, and then grind and disperse with a three-roll mill to obtain a high thermal conductivity aluminum paste with a scraping fineness < 5 μm.

[0049] 3. Print the conductive copper paste prepared above on a 2 mm ordinary glass slide with a corresponding pattern using a silk screen to obtain a glass slide printed with the conductive copper paste.

[0050] 4. Place the glass slides prepared above into a forced-air drying oven and bake them at 120 °C for 15 minutes to form the shape.

[0051] 5. Print the prepared high thermal conductivity aluminum paste on the back of the glass slide printed with the conductive copper paste above, and then place it in the forced-air drying oven again to bake and form the shape, obtaining a glass slide printed with the conductive copper paste and the thermal conductivity aluminum paste.

[0052] 6. Subject the glass slide printed with the conductive copper paste and the thermal conductivity aluminum paste above to degumming and pre-curing in a muffle furnace at 400 °C for 20 minutes.

[0053] 7. Put the above-mentioned debinded glass sheet into a hydrogen-nitrogen mixed atmosphere furnace, sinter and reduce it at 700 °C for 20 min to obtain a high-thermal-conductivity copper circuit glass-based circuit board.

[0054] Example 3

[0055] A preparation method of a copper circuit glass-based circuit board includes the following steps:

[0056] 1. Weigh 81 g of copper powder with a particle size of 0.3 - 0.5 μm, 9 g of glass powder, 6 g of diethylene glycol monobutyl ether, 2 g of dodecyl alcohol ester, 0.5 g of ethyl cellulose, 0.9 g of dispersant, and 0.6 g of thixotropic agent respectively, add them into a container, pre-stir and mix, and then grind and disperse with a three-roll grinder to obtain a conductive copper paste with a scraping fineness < 5 μm.

[0057] 2. Weigh 80.75 g of aluminum powder with a particle size of 1 - 2 μm, 4.25 g of glass powder, 8 g of diethylene glycol monobutyl ether, 4.65 g of dodecyl alcohol ester, 1.2 g of ethyl cellulose, 0.85 g of dispersant, and 0.3 g of thixotropic agent respectively, add them into a container, pre-stir and mix, and then grind and disperse with a three-roll grinder to obtain a high-thermal-conductivity aluminum paste with a scraping fineness < 5 μm.

[0058] 3. Screen-print the above-prepared conductive copper paste on a 2-mm high aluminum glass sheet with a corresponding pattern to obtain a glass sheet printed with the conductive copper paste.

[0059] 4. Put the above-prepared glass sheet into a forced-air drying oven and bake it at 120 °C for 15 min to form a shape.

[0060] 5. Print the above-prepared high-thermal-conductivity aluminum paste on the back of the glass sheet printed with the conductive copper paste, and then put it into the forced-air drying oven again to bake and form a shape to obtain a glass sheet printed with the conductive copper paste and the thermal-conductivity aluminum paste.

[0061] 6. Put the glass sheet printed with the conductive copper paste and the thermal-conductivity aluminum paste into a muffle furnace and carry out debinding and pre-curing at 400 °C for 20 min.

[0062] 7. Put the above-mentioned debinded glass sheet into a hydrogen-nitrogen mixed atmosphere furnace, sinter and reduce it at 700 °C for 20 min to obtain a high-thermal-conductivity copper circuit glass-based circuit board.

[0063] Example 4

[0064] A preparation method of a copper circuit glass-based circuit board includes the following steps:

[0065] 1. Weigh 81 g of copper powder with a particle size of 0.3 - 0.5 μm, 9 g of glass powder, 6 g of diethylene glycol monobutyl ether, 2 g of dodecyl alcohol ester, 0.5 g of ethyl cellulose, 0.9 g of dispersant, and 0.6 g of thixotropic agent into a container, pre-stir and mix them, and then grind and disperse them with a three-roll grinder to obtain a conductive copper paste with a blade fineness < 5 μm;

[0066] 2. Weigh 80.75 g of aluminum powder with a particle size of 1 - 2 μm, 4.25 g of glass powder, 8 g of diethylene glycol monobutyl ether, 4.65 g of dodecyl alcohol ester, 1.2 g of ethyl cellulose, 0.85 g of dispersant, and 0.3 g of thixotropic agent into a container, pre-stir and mix them, and then grind and disperse them with a three-roll grinder to obtain a highly thermally conductive aluminum paste with a blade fineness < 5 μm;

[0067] 3. Screen-print the above-prepared conductive copper paste on a 1-mm-high aluminum glass sheet with a corresponding pattern to obtain a glass sheet printed with the conductive copper paste;

[0068] 4. Put the above-prepared glass sheet into a forced-air drying oven and bake it at 120 °C for 15 min to form a shape;

[0069] 5. Print the above-prepared highly thermally conductive aluminum paste on the back of the glass sheet printed with the conductive copper paste, and then put it into the forced-air drying oven again to bake and form a shape to obtain a glass sheet printed with the conductive copper paste and the thermally conductive aluminum paste;

[0070] 6. Subject the above glass sheet printed with the conductive copper paste and the thermally conductive aluminum paste to degumming and pre-curing in a muffle furnace at 400 °C for 20 min;

[0071] 7. Put the above degummed glass sheet into a hydrogen-nitrogen mixed atmosphere furnace and sinter and reduce it at 700 °C for 20 min to obtain a highly thermally conductive copper circuit glass-based circuit board.

[0072] Example 5

[0073] A preparation method of a copper circuit glass-based circuit board includes the following steps:

[0074] 1. Weigh 81 g of copper powder with a particle size of 0.3 - 0.5 μm, 9 g of glass powder, 6 g of diethylene glycol monobutyl ether, 2 g of dodecyl alcohol ester, 0.5 g of ethyl cellulose, 0.9 g of dispersant, and 0.6 g of thixotropic agent into a container, pre-stir and mix them, and then grind and disperse them with a three-roll grinder to obtain a conductive copper paste with a blade fineness < 5 μm;

[0075] 2. Weigh 80.75 g of aluminum powder with a particle size of 0.5 μm, 4.25 g of glass powder, 8 g of diethylene glycol monobutyl ether, 4.65 g of dodecyl alcohol ester, 1.2 g of ethyl cellulose, 0.85 g of dispersant, and 0.3 g of thixotropic agent into a container, pre-stir and mix them, and then grind and disperse them with a three-roll grinder to obtain a highly thermally conductive aluminum paste with a blade fineness < 5 μm;

[0076] 3. Screen-print the above-prepared conductive copper paste on a 1-mm high-aluminum glass sheet with a corresponding pattern to obtain a glass sheet printed with the conductive copper paste.

[0077] 4. Place the above-prepared glass sheet in a forced-air drying oven and bake it at 120 °C for 15 min to form a shape.

[0078] 5. Print the above-prepared high-thermal-conductivity aluminum paste on the back of the above glass sheet printed with the conductive copper paste, and then place it in the forced-air drying oven again to bake and form a shape, obtaining a glass sheet printed with the conductive copper paste and the thermal-conductivity aluminum paste.

[0079] 6. Subject the above glass sheet printed with the conductive copper paste and the thermal-conductivity aluminum paste to degumming and pre-curing in a muffle furnace at 400 °C for 20 min.

[0080] 7. Place the above degummed glass sheet in a hydrogen-nitrogen mixed atmosphere furnace, sinter and reduce it at 700 °C for 20 min to obtain a high-thermal-conductivity copper circuit glass-based circuit board.

[0081] Example 6

[0082] A method for preparing a nickel circuit glass-based circuit board includes the following steps:

[0083] 1. Weigh 83.3 g of 5-μm nickel powder, 1.7 g of glass powder, 8 g of diethylene glycol monobutyl ether, 4.8 g of dodecyl alcohol ester, 0.75 g of ethyl cellulose, 0.85 g of dispersant, and 0.6 g of thixotropic agent and add them to a container, pre-stir and mix them, and then grind and disperse them with a three-roll mill to obtain a conductive nickel paste with a blade fineness < 10 μm.

[0084] 2. Weigh 80.75 g of 0.5-μm aluminum powder, 4.25 g of glass powder, 8 g of diethylene glycol monobutyl ether, 4.65 g of dodecyl alcohol ester, 1.2 g of ethyl cellulose, 0.85 g of dispersant, and 0.3 g of thixotropic agent and add them to a container, pre-stir and mix them, and then grind and disperse them with a three-roll mill to obtain a high-thermal-conductivity aluminum paste with a blade fineness < 5 μm.

[0085] 3. Screen-print the above-prepared conductive nickel paste on a 1-mm high-aluminum glass sheet with a corresponding pattern to obtain a glass sheet printed with the conductive nickel paste.

[0086] 4. Place the above-prepared glass sheet in a forced-air drying oven and bake it at 120 °C for 15 min to form a shape.

[0087] 5. Print the above-prepared high-thermal-conductivity aluminum paste on the back of the above glass sheet printed with the conductive nickel paste, and then place it in the forced-air drying oven again to bake and form a shape, obtaining a glass sheet printed with the conductive nickel paste and the thermal-conductivity aluminum paste.

[0088] 6. Place the glass sheet printed with conductive nickel paste and thermally conductive aluminum paste into a muffle furnace, sinter at 700 °C for 10 min in an air atmosphere to obtain a nickel circuit glass-based circuit board with high thermal conductivity.

[0089] Comparative Example 1

[0090] A preparation method of a copper circuit glass-based circuit board includes the following steps:

[0091] 1. Weigh 81 g of copper powder with a particle size of 0.3 - 0.5 μm, 9 g of glass powder, 6 g of diethylene glycol monobutyl ether, 2 g of dodecyl alcohol ester, 0.5 g of ethyl cellulose, 0.9 g of dispersant, and 0.6 g of thixotropic agent and add them into a container, pre-stir and mix, and then grind and disperse with a three-roll mill to obtain a conductive copper paste with a scraping fineness < 5 μm.

[0092] 2. Screen-print the above-prepared conductive copper paste on a 2-mm ordinary glass sheet with a corresponding pattern to obtain a glass sheet printed with conductive copper paste.

[0093] 3. Place the above-prepared glass sheet into a forced-air drying oven and bake it at 120 °C for 15 min to form a shape.

[0094] 4. Place the glass sheet printed with conductive copper paste after baking into a muffle furnace and degum and pre-cure it at 400 °C for 20 min.

[0095] 5. Place the glass sheet after degumming into a hydrogen-nitrogen mixed atmosphere furnace, sinter and reduce it at 700 °C for 20 min to obtain a copper circuit glass-based circuit board.

[0096] Comparative Example 2

[0097] A preparation method of a copper circuit glass-based circuit board includes the following steps:

[0098] 1. Weigh 81 g of copper powder with a particle size of 0.3 - 0.5 μm, 9 g of glass powder, 6 g of diethylene glycol monobutyl ether, 2 g of dodecyl alcohol ester, 0.5 g of ethyl cellulose, 0.9 g of dispersant, and 0.6 g of thixotropic agent and add them into a container, pre-stir and mix, and then grind and disperse with a three-roll mill to obtain a conductive copper paste with a scraping fineness < 5 μm.

[0099] 2. Screen-print the above-prepared conductive copper paste on a 2-mm high-aluminum glass sheet with a corresponding pattern to obtain a glass sheet printed with conductive copper paste.

[0100] 3. Place the above-prepared glass sheet into a forced-air drying oven and bake it at 120 °C for 15 min to form a shape.

[0101] 4. Place the glass sheet printed with conductive copper paste after baking into a muffle furnace and degum and pre-cure it at 400 °C for 20 min.

[0102] 5. Place the above debound glass sheet into a hydrogen-nitrogen mixed atmosphere furnace, sinter and reduce it at 700 °C for 20 min to obtain a copper circuit glass-based circuit board.

[0103] Comparative Example 3

[0104] A preparation method of a copper circuit glass-based circuit board includes the following steps:

[0105] 1. Weigh 81 g of copper powder with a particle size of 0.3 - 0.5 μm, 9 g of glass powder, 6 g of diethylene glycol monobutyl ether, 2 g of dodecyl alcohol ester, 0.5 g of ethyl cellulose, 0.9 g of dispersant, and 0.6 g of thixotropic agent respectively and add them into a container. Pre-stir and mix them, and then grind and disperse them with a three-roll grinder to obtain a conductive copper paste with a scraping fineness < 5 μm.

[0106] 2. Screen-print the above-prepared conductive copper paste on a 1-mm high-aluminum glass sheet with a corresponding pattern to obtain a glass sheet printed with the conductive copper paste.

[0107] 3. Place the above-prepared glass sheet into a forced-air drying oven and bake it at 120 °C for 15 min to form a shape.

[0108] 4. Place the above glass sheet printed with the conductive copper paste into a muffle furnace and carry out debinding and pre-curing at 400 °C for 20 min.

[0109] 5. Place the above debound glass sheet into a hydrogen-nitrogen mixed atmosphere furnace, sinter and reduce it at 700 °C for 20 min to obtain a common copper circuit glass-based circuit board.

[0110] Comparative Example 4

[0111] A preparation method of a nickel circuit glass-based circuit board includes the following steps:

[0112] 1. Weigh 83.3 g of nickel powder with a particle size of 5 μm, 1.7 g of glass powder, 8 g of diethylene glycol monobutyl ether, 4.8 g of dodecyl alcohol ester, 0.75 g of ethyl cellulose, 0.85 g of dispersant, and 0.6 g of thixotropic agent respectively and add them into a container. Pre-stir and mix them, and then grind and disperse them with a three-roll grinder to obtain a conductive nickel paste with a scraping fineness < 10 μm.

[0113] 2. Screen-print the above-prepared conductive nickel paste on a 1-mm high-aluminum glass sheet with a corresponding pattern to obtain a glass sheet printed with the conductive nickel paste.

[0114] 3. Place the above glass sheet printed with the nickel paste into a forced-air drying oven and bake it at 120 °C for 15 min to form a shape.

[0115] 4. Place the above glass sheet with the baked shape into a muffle furnace and sinter it in an air atmosphere at 700 °C for 10 min to obtain a nickel circuit glass-based circuit board.

[0116] Performance Analysis

[0117] The thermal conductivity coefficients of the glass-based circuit boards prepared in the above examples and comparative examples were tested respectively, and the results are as follows:

[0118] Table 1

[0119]

[0120]

[0121] It can be seen from the test results in Table 1 above that after coating a layer of high thermal conductivity aluminum paste on the back of the glass-based circuit board, whether it is a common glass-based circuit board or a high-aluminum glass-based circuit board, its thermal conductivity coefficient has been significantly improved compared with the glass-based circuit board without coating high thermal conductivity aluminum paste in the comparative example. Among them, the glass-based circuit board prepared in Example 5 has the best thermal conductivity coefficient. This is because the aluminum paste with high thermal conductivity used in Example 5 has smaller particles and a high solid content. After sintering, the inside of the aluminum paste with high thermal conductivity is denser, forming a good thermal conduction network, so the thermal conductivity of the thermal conduction layer is better. In the comparative example, since the thermal conductivity aluminum paste was not printed on the back of the glass-based circuit board, its thermal conductivity is determined by the thermal conductivity of the glass substrate itself. For the same composition of glass, the thicker the thickness, the worse the thermal conductivity; among the glasses with the same thickness, the high-aluminum glass has better thermal conductivity than the common glass. Due to the stress during the sintering process of the conductive paste and the aluminum paste with high thermal conductivity, the glass substrate warps and deforms. Therefore, the thickness of the glass cannot be too thin. When the thickness is less than 1 mm, the warpage rate is too high, resulting in a decrease in the product qualification rate.

[0122] The above are only the preferred embodiments of the present application and are not intended to limit the present application. Any modifications, equivalent replacements, and improvements made within the spirit and principle of the present application shall be included in the protection scope of the present application.

Claims

1. A method for preparing a glass substrate, characterized in that, it comprises the following steps: providing an initial glass substrate, and the initial glass substrate is selected from glass sheets with a thickness of 1 mm; preparing a conductive pattern on one surface of the initial glass substrate; coating a high thermal conductivity aluminum paste on the back surface of the initial glass substrate with the conductive pattern formed thereon as a heat conduction area, performing a drying treatment, then performing a degumming pre-curing treatment at 400 °C for 20 min, and then performing a co-sintering at 700 °C for 20 min to obtain a glass substrate; wherein, based on the total weight of the aluminum paste being 100%, it comprises the following components in weight percentage: 80.75% of aluminum powder, 4.25% of glass powder, 8% of diethylene glycol monobutyl ether, 4.65% of dodecyl alcohol ester, 1.2% of ethyl cellulose, 0.85% of dispersant, 0.3% of thixotropic agent; the size of the aluminum powder is 0.5 μm.

2. The method for preparing a glass substrate according to claim 1, characterized in that, the drying treatment is baking at 80 - 200 °C.

3. The method for preparing a glass substrate according to any one of claims 1 to 2, characterized in that, the step of preparing a conductive pattern on one surface of the initial glass substrate comprises: printing a conductive paste on the initial glass substrate through a pattern screen, and then baking at 80 - 200 °C.

4. The method for preparing a glass substrate according to claim 3, characterized in that, the pattern screen is a wire mesh or a steel mesh.

5. The method for preparing a glass substrate according to claim 3, characterized in that, based on the total weight of the conductive paste being 100%, the conductive paste comprises the following components in weight percentage: 70 - 90% of metal powder, 0.5 - 20% of inorganic binder, 5 - 15% of organic solvent, 0 - 5% of film-forming aid, 0 - 5% of other additives.

6. The method for preparing a glass substrate according to claim 5, characterized in that, the metal powder is selected from at least one of copper powder, silver powder, aluminum powder and nickel powder.

7. The method for preparing a glass substrate according to claim 5, characterized in that, the inorganic binder is a glass powder with a softening point of 300 - 650 °C; the organic solvent is selected from at least one of diethylene glycol monobutyl ether, diethylene glycol butyl ether acetate, terpineol and dodecyl alcohol ester; and / or, the film-forming aid is selected from at least one of ethyl cellulose, acrylic resin and cellulose acetate butyrate; and / or, the other additives are selected from at least one of dispersant, thixotropic agent, leveling agent and defoaming agent.

Citation Information

Patent Citations

  • Method for additive manufacturing of glass substrate PCB and LED display

    CN111328192A

  • Method of manufacturing electrical device

    CN113130707A

  • Light emitting device and lighting apparatus

    US20160265758A1